Propofol and sufentanil may affect the patients’ sleep quality independently of the surgical stress response: a prospective nonrandomized controlled trial in 1033 patients’ undergone diagnostic upper gastrointestinal endoscopy - Ming Lei; Peng Zhang; Yunfei Liu; Fangfang Fu; Ling Ye; Tao Zhu (BMC Anesthesiology, 2017)
Abstract Background It is unknown whether sedative per se contributes to the postoperative sleep disturbance. Diagnostic upper gastrointestinal endoscopy (UGE) is a minimally invasive procedure which is not likely to cause tissue trauma and pain. The purpose of this study was to evaluate the sleep quality of patients undergoing routine (without sedative) diagnostic UGE or UGE with sedative, before, 1 week, and 1 month after the procedure. Methods One thousand and thirty-three patients undergoing UGE were enrolled. Patients chose sedative or without sedative. Propofol and sufentanil were administered to the sedative group, not allowed for the routine group. The Pittsburgh Sleep Quality Index (PSQI) was measured before, 1 week and 1 month after the procedure. Results Five hundred and ten patients were enrolled in the sedative group and 523 in the routine group. One week after the procedure, patients in the sedative group showed significantly higher PSQI scores (worse sleep quality) than the baseline PSQI scores (p < 0.001), but there was no significant change for the routine group in the same period (p = 0.096). One month after the procedure, there was no significant difference in PSQI scores between the two groups compared with the baseline values (p = 0.358 for sedative group, p = 0.161 for routine group). There were also no significant difference in the PSQI scores between the two groups in the entire 1 month follow-up period (p = 0.885). Conclusions The sedative group showed impaired sleep quality 1 week after diagnostic UGE. Propofol and sufentanil may independently affect the sleep quality of patients after sedative of diagnostic UGE for only one week. Trial registration This study is registered on Chinese Clinical Trial Registry ( IDChiCTR-OCH-13003128 ). Registered 2 April 2013.